2022
DOI: 10.1038/s41598-022-21979-7
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of microbial resistance in bloodstream infections of hemodialysis patients: a cross-sectional study from Palestine

Abstract: Bloodstream infections (BSIs) are a prominent cause of death and hospitalization among hemodialysis (HD) patients. The emergence of multidrug-resistant organisms (MDRO) is making the management of these infections more challenging. This study describes the clinical characteristics, microbial profiles and antibiotic resistance patterns in patients with BSIs. A retrospective cross-sectional study was conducted at An-Najah National University Hospital from January 2019 to December 2020. Clinical and demographic d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 34 publications
1
10
0
Order By: Relevance
“…Few studies have been conducted on the use of antibiotics in hospitals in Palestine [ 16 18 ], and none have looked at FN. Therefore, this study aims to determine antimicrobial resistance among cancer patients who developed FN from chemotherapy in a tertiary academic hospital in Palestine.…”
Section: Introductionmentioning
confidence: 99%
“…Few studies have been conducted on the use of antibiotics in hospitals in Palestine [ 16 18 ], and none have looked at FN. Therefore, this study aims to determine antimicrobial resistance among cancer patients who developed FN from chemotherapy in a tertiary academic hospital in Palestine.…”
Section: Introductionmentioning
confidence: 99%
“…has been the most commonly isolated organism from blood culture leading prescribers to use vancomycin accounting for 40%–75% of all positive blood cultures. 32 , 33 Variations in recommendations when it comes to blood culture sampling exist. In adults, if concerned about a central venous catheter (CVC)-related infection, the Infectious Disease Society of America (IDSA) guidelines recommend to obtain a set of peripheral and a set from central lines.…”
Section: Methods and Resultsmentioning
confidence: 99%
“…There were few studies that assessed the prevalence and pattern of sensitivity of bloodstream infections in our institution. One of them was a 2-year study among hemodialysis patients, which concluded that 99 (83.89%) of the isolated blood culture pathogens were gram-positive and 19 (16.1%) were gram-negative [ 12 ]. Another study in our institution among solid tumor patients revealed that the most common source of positive blood cultures was catheter-related.…”
Section: Discussionmentioning
confidence: 99%